Sustainable Farming Systems in the Sub-Sahelian Zone of Burkina Faso -: Key Factors - Hien, E. -; Kabore, W. T. -; Masse, D. -; Dugue, P. (Sustainability in Debate, 2010)
Rapid population growth and climatic change threatens the sustainability of natural resources. Farming practices can mitigate environmental change and degradation. The aim of this research conducted in Yatenga region was to describe and to analyse manure practices management. In 2005, a survey was carried out to assess the evolution of farming practices. A survey was initially conducted with a sample of 44 farmers, selected randomly in the three neighbouring villages. Subsequently, 18 farms were selected for in-depth interviews. The grain yield was measured and the different practices of soil and water conservation developed by farmers were compared. According to the enquiries, two practices, called “zaï” and “djengo”, were largely used in cereals production. The “zaï” practice, known as a traditional technique for restoration of degraded soil, is characterized by the capture of runoff by micro-watersheds and a localized organic matter supply at the soil-plant system scale. The “djengo” practice is based on the same principle of the “zaï” practice but was applied on the sandy soil as traditionally “zaï” concerned the degraded and crusty soils. The two practices could increase grain crop production but moreover could limit the risk of crops failure. In addition, our observations also showed that frequent tree regenerations occurred in plots and watersheds where “zaï” or “djengo” practices were used. This study highlights the necessity of better controlling soil, water and organic matter to improve agrosystem sustainability in sub Saharan Africa.